Knowledge, language, and silence : selected papers - Dąmbska, Izydora. (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2016)
Izydora Dąmbska (1904-1982) was a Polish philosopher; a student of Kazimierz Twardowski, and his last assistant. Her output consists of almost 300 publications. The main domains of her research were semiotics, epistemology and broadly understood methodology as well as axiology and history of philosophy. Dąmbska's approach to philosophical problems reflected tendencies that were characteristic of the Lvov-Warsaw School. She applied high methodological standards but has never limited the domain of analyzed problems in advance. The present volume includes twenty-eight translations of her representative papers. As one of her pupils rightly wrote: "Dąmbska's works may help everyone [...] to think clearly. Her attitude of an unshaken philosopher may help anyone to hold oneself straight, and, if necessary, to get up after a fall".